Relic abundance of mass-varying cold dark matter particles - Rosenfeld, Rogério [UNESP] (Elsevier B.V., 2005)
In models of coupled dark energy and dark matter the mass of the dark matter particle depends on the cosmological evolution of the dark energy field. In this Letter we exemplify in a simple model the effects of this mass variation on the relic abundance of cold dark matter. (c) 2005 Elsevier B.V. All rights reserved.